THE RECONSTRUCTION OF ISLAMIC THEOLOGY IN THE UNITY OF SCIENCES - Yusriyah, Yusriyah (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
As a result of the processes of thinking on theological concept, Islamic theology may change according to its social dynamics. In the contemporary, theology can be studied by interdisciplinary sciences, which eventually theology became the source of the birth of some sciences. Hence, the science produced by the understanding of monotheism will produce peaceful religion for the universe (raḥmatan li ’l-‘ālamīn). The data presented in this article derived from the study applying literature review on the related topics of writing. Applying qualitative approach, this article showed that religion and science have a point of tangency. Science helps to facilitate human beings in their religious living. Concerning to faith, science activities can strengthen the faith and arise the motivation to express something in recognizing more toward God as the center of unity of existence (tawḥīd). In order to integrate the belief and sciences, it is needed the effort of islamization of science and the effort to reconstruct theology into a format that make it possible to dialogue with the reality of current development of thinking.***Sebagai hasil dari pemikiran konsep teologis teologi Islam dapat berubah sesuai dengan dinamika sosial. Dalam era kontemporer teologi dapat dikaji oleh ilmu-ilmu interdisipliner, yang akhirnya teologi merupakan sumber lahirnya beberapa ilmu sehingga ilmu yang dihasilkan oleh pemahaman tawḥīd akan menghasilkan agama damai bagi alam semesta (raḥmatan li ’l-‘ālamīn). Data yang disajikan dalam artikel ini berasal dari penelaahan terhadap literatur yang terkait dengan topik penulisan. Dengan pendekatan kualitatif artikel ini menunjukkan bahwa agama dan sains memiliki titik singgung. Ilmu membantu memfasilitasi manusia dalam kehidupan keagamaannya. Dengan iman, kegiatan ilmiah dapat memperkuat iman dan membuat motivasi untuk mengekspresikan sesuatu yang dapat menambah pengakuan terhadap Allah sebagai pusat kesatuan eksistensi (tawḥīd). Untuk mewujudkan ketersinggungan antara iman dan ilmu maka perlu islamisasi ilmu pengetahuan dan juga dalam upaya untuk merekonstruksi teologi ke format yang dapat berdialog dengan realitas perkembangan pemikiran yang berlangsung hari ini.